2015
DOI: 10.1007/s13592-015-0394-6
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and molecular detection of Nosema spp. in honeybees of Turkey

Abstract: -In this study, we aimed to determine the prevalence of Nosema spp. in honeybees of Turkey. For this aim, adult honeybee (Apis mellifera ) samples were collected from 1621 colonies within 95 apiaries located in 22 provinces of Turkey. Samples were examined microscopically. In case of positivity, spore identification was done by multiplex PCR. At the end of microscopic examination, Nosema spp. spores were detected in 7 out of 22 provinces (31.8 %), and 16 out of 95 colonies (16.8 %) that represent 1621 colonies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Again, in cases in which BQCV and N. apis were seen simultaneously, there is no precise information on the presence of clinical signs. This situation seems to support other studies that indicated that N. apis is less pathogenic compared to N. ceranae (8,36).…”
Section: Gattgtgcggcttaatttgactcaacgcgaggtaacttaccaatattttsupporting
confidence: 91%
See 1 more Smart Citation
“…Again, in cases in which BQCV and N. apis were seen simultaneously, there is no precise information on the presence of clinical signs. This situation seems to support other studies that indicated that N. apis is less pathogenic compared to N. ceranae (8,36).…”
Section: Gattgtgcggcttaatttgactcaacgcgaggtaacttaccaatattttsupporting
confidence: 91%
“…As a result of PCR performed with specific primers that replicated the 16S rRNA gene region, Tosun (35) reported only the presence of N. ceranae in the province of Ordu. Utuk et al (36) reported Nosema ceranae as the dominant species in Turkey using the PCR method. In this study, while Nosema ceranae was detected in adult honeybees as a result of PCR in 5 apiaries in the province of Van, no N. apis or mixed N. apis/N.…”
Section: Gcaagattgaaaattaaagaaattgacggaagaataccacaaggagtg Gattgtgcggcttaatttgactcaacgcgaggtaacttaccaatattttmentioning
confidence: 99%
“…One N. ceranae spore observed in the entire hemocytometer’s grid (25 × 16 = 400 small squares) was equal to an average of 1500 spores per bee. The reported information was the number of spores per bee [ 112 ].…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of Nosema infection was first described in 1986 in Turkey (Tutkun & Inci, 1992), and, so far, the infestation rate has been reported in different ratios such as 26.4%, 60%, 45.8% in 1990, 2005, 2016 respectively (Kutlu & Kaftanoğlu, 1990;Aydın et al, 2001;Özkırım et al, 2019). One of the studies conducted in Ankara showed the existence of nosemosis and 93.75% prevalence of N. ceranae and 6.25% N. apis infection (Utuk et al, 2016).…”
Section: Discussionmentioning
confidence: 99%